Introduction: The Laurentide Ice Sheet and its Significance - Fulton, Robert; Prest, Victor (Géographie physique et Quaternaire, 1987)
ABSTRACTThe Laurentide Ice Sheet is a glacier complex that covered large parts of eastern, central and northern North America during the last glaciation. The Ice Sheet depressed the crust by at least 300 m and it held enough water to lower sea level 40-50 m. The Laurentide Ice Sheet was first viewed as a complex of essentially independent glaciers; later it was considered a single sheet centred on Hudson Bay; and recently the Laurentide Ice Sheet has been shown to have been made up of at least 3 major coalescent ice masses. In addition to lowering sea level and depressing the land surface, it changed atmospheric circulation, caused southward movement of biozones, eroded the weathered mantle, and deposited extensive areas of freshly eroded materials. Understanding the history and dynamics of the Ice Sheet is important in prospecting for more deposits, predicting effects of acid rain, understanding the nature and distribution of soils, locating granular aggregate, predicting sea level change, modelling climatic change and predicting major changes in flow patterns of modern ice sheets.